Faktor-faktor yang Memengaruhi Resiliensi Remaja Pasca Dating Violence: Sebuah Studi Literatur - Divariani Putu; Wulan Budisetyani I Gusti Ayu Putu (Humanitas (Jurnal Psikologi), 2023)
Cases of dating violence have continued to occur in recent years. Dating violence in pandemic situations has a significant impact on adolescents that can lead to anxiety and depression, so resilience is very crucial. The process of resilience is influenced by the internal and external factors of adolescents during and after facing dating violence.  The data collection method in this paper uses a descriptive literature study on secondary data from 2016-2021. This paper aims to provide a reference for adolescents who experience dating violence so they can overcome the difficulties that occur and rise from the worst experiences and become resilient individuals who are free from psychological problems in the future. The findings of this descriptive literature study indicate that the resilience process is influenced by the presence of internal and external factors during and after the occurrence of teen dating violence.